(untitled) (SCIENCE TIME JOURNAL, 2026)
This study investigates metadiscourse as a central mechanism of academic legitimization in English and Uzbek research articles. The research examines how metadiscursive resources regulate argumentative organization, guide reader interpretation, and construct epistemic credibility across two distinct scholarly traditions. Drawing on a comparative discourse analytical framework, the study analyzes interactional and textual metadiscourse in selected research articles from humanities and social sciences disciplines. The findings reveal that in English academic writing metadiscourse frequently functions through dialogic engagement, calibrated epistemic positioning, and explicit reader orientation. In contrast, Uzbek research articles demonstrate a stronger reliance on structural coherence, cumulative reasoning, and integrative generalization as mechanisms of legitimization. Despite these differences, both discourse traditions employ metadiscourse as a regulatory layer that aligns argumentative development with culturally embedded models of scholarly authority. The study proposes a linguopragmatic model of academic legitimization in which metadiscourse mediates between argumentative structuring and epistemic evaluation. The findings contribute to cross linguistic discourse studies by clarifying how academic credibility is discursively constructed within different communicative frameworks.